IMPLEMENTASI KAMPUS ISLAMI RAMAH HAM DENGAN MENERAPKAN NILAI-NILAI TOLERANSI DAN SOLIDARITAS DI DUNIA PENDIDIKAN - Ahmad Ruslan; Mubarak Ahmad; Desvian Bandarsyah; Herdin Muhtarom; Anang Rizki Usahawanto; Gery Erlangga (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2022)
Campus as an educational institution that aims to create individuals who are ready to plunge into public life directly have a responsibility in educating individuals to have humanist nature. Starting from the problem, the author is interested in reviewing the implementation of human rights-friendly Islamic campuses by applying the values of tolerance and solidarity. This study uses qualitative research type with Mixed-Methods method with samples of FKIP UHAMKA students. The results obtained in this study are that FKIP UHAMKA students already have a basic understanding of human rights that can be seen from student activities on campus that uphold the values of tolerance and solidarity.